The royal doctors, 1485-1714 : medical personnel at the Tudor and Stuart courts - Furdell, Elizabeth Lane (University of Rochester Press, 2001)
Drawing upon a myriad of primary and secondary historical sources, The Royal Doctors: Medical Personnel at the Tudor and Stuart Courts investigates the influential individuals who attended England's most important patients during a pivotal epoch in the evolution of the state and the medical profession. Over three hundred men (and a handful of women), heretofore unexamined as a group, made up the medical staff of the Tudor and Stuart kings and queens of England (as well as the Lord Protectorships of Oliver and Richard Cromwell). The royal doctors faced enormous challenges in the sixteenth and seventeenth centuries from diseases that respected no rank and threatened the very security of the realm. Moreover, they had to weather political and religious upheavals that led to regicide and revolution, as well as cope with sharp theoretical and jurisdictional divisions within English medicine. The rulers often interceded in medical controversies at the behest of their royal doctors, bringing sovereign authority to bear on the condition of medicine.